Estimasi Laju Erosi Pada Beberapa Daerah Tangkapan Air Waduk Di Daerah Aliran Sungai Bengawan Solo Dengan Sistem Informasi Geografi - Sri Mulat Yuningsih; Bayu Raharja; Irfan Sudono; Fauzi Fauzi (Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2012)
Soil affected by erosion will be carried by the flow of surface water into the river and would enter into the reservoir. This causes siltation of reservoirs that have done studies to estimate the amount of erosion rate in this case performed on Dawuhan Reservoir Catchment Area, Gondang Reservoir, and Nglambangan Reservoir, Bengawan Solo River Basin. One method often used in measuring the level of vulnerability to erosion is a method of USLE (Universal Soil Loss Equation). Erosion prediction with USLE method can also use GIS in its calculations. Geographic Information System (GIS) is a spatially-based technologies that are very popular today. Utilization of GIS-based spatial modeling pixels as a tool in predicting erosion can help the accuracy of the data generated, especially on lands that have a complex topography. The results of the analysis can be concluded greatest erosion rate occurred in the catchment areas of Nglambangan Reservoir with 75,327.93 tons / year with erosion rate27,18 tons/Ha/year. The rate of erosion found on the location of the second largest Gondang Reservoir with a total annual erosion rate of 7,347.77 tons / year with erosion rate 3,08 tons/Ha/year.